MANDE RUBIAH: OBJEK DAYA TARIK WISATA EDUKASI DAN BUDAYA DI PESISIR SELATAN - ALDO, APRIN (JURNAL KEILMUAN TEKNOLOGI DAN PENDIDIKAN TERPADU, 2025)
Mande Rubiah is one of the cultural tourism destinations that holds significant historical value and strong traditional heritage in Pesisir Selatan Regency, West Sumatra. This study aims to describe the historical development of tourism in Mande Rubiah, identify its tangible and intangible tourism attractions, and analyze the character values embedded in the cultural practices of the Lunang community. Employing a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The findings indicate that Mande Rubiah originates from the historical narrative of Bundo Kanduang’s arrival in Lunang, which led to the establishment of the rumah gadang as a center of cultural and customary activities. The site’s main attractions include historical artefacts, traditional architectural structures, and preserved customary rituals and religious traditions. Character values such as religiosity, honesty, responsibility, social care, and affection for local culture form an integral part of Mande Rubiah’s identity. These findings contribute to the development of cultural tourism in Pesisir Selatan and serve as a foundation for community-based cultural heritage preservation strategies.